2011
DOI: 10.1159/000323928
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Non-Alcoholic Steatohepatitis and Basis for Treatment

Abstract: Non-alcoholic fatty liver disease (NAFLD) is likely the most common cause of liver disease in adults as well as in children and adolescents. Its occurrence is closely associated with obesity and insulin resistance. NAFLD may lead to non-alcoholic steatohepatitis (NASH) with possible evolution towards cirrhosis and hepatocellular carcinoma. In addition to steatosis, NASH is characterized by necroinflammation and fibrosis. While the presence of simple steatosis can be assessed by imaging studies, the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 109 publications
0
34
0
Order By: Relevance
“…Very few breakthroughs have, however, occurred in therapeutic intervention of this disease. 9 Research developing novel, safe, and effective anti-fibrotic strategies is, thus, of the highest priority. 10 Hepatic stellate cells (HSC) are the major effectors during hepatic fibrogenesis.…”
mentioning
confidence: 99%
“…Very few breakthroughs have, however, occurred in therapeutic intervention of this disease. 9 Research developing novel, safe, and effective anti-fibrotic strategies is, thus, of the highest priority. 10 Hepatic stellate cells (HSC) are the major effectors during hepatic fibrogenesis.…”
mentioning
confidence: 99%
“…Another potential mechanism by which NAFLD may increase CVD risk is abnormal lipoprotein metabolism. Therefore, enhanced oxidative stress, inflammation with release of inflammatory cytokines and abnormal lipoprotein metabolism could account for the proatherogenic effect of NAFLD [5,13,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin, leptin, TNF-α, and IL-6 play critical roles in the process of inflammation and liver injury 52 ( Figure 1). Several studies have demonstrated that autophagy exhibits cellular protective effects, leading cells to survival from death stimuli.…”
Section: Autophagy and Steatohepatitismentioning
confidence: 99%